Evaluation of the functionality of bread loaves prepared with quinoa flakes through biological tests (Brazilian Journal of Pharmaceutical Sciences, 2016)
The aim of this study was to evaluate quinoa flakes and bread prepared with the pseudocereal with regard to nutritional aspects by determining chemical composition, content of tocopherols and fatty acid composition as well as to possible beneficial effects in Wistar rats given commercial feed supplemented or not with quinoa flakes and cholesterol. The following parameters were determined: weight gain, food intake, liver weight, fat in liver and lipid profile in blood and liver. The results showed that processing affected the nutritional characteristics of bread because there was a significant increase in dietary fiber content but reduction in soluble fiber. Increased fiber did not influence food intake or weight gain. Regarding fat in liver of rats, the group that consumed bread without quinoa but with cholesterol showed higher lipid content. The addition of quinoa increased significantly the level of all types of tocopherols, especially in the group of animals that consumed 20% quinoa bread, improving the lipid profile both in blood and liver, largely due to a reduction in oxidized LDL.